Left cerebellar lesions may be associated with an increase in spatial neglect-like symptoms - Verbitsky, Ryan; Anderson, Britt; Danckert, James; Dukelow, Sean; Striemer, Christopher (My University, 2023)
Each cerebellar hemisphere projects to the contralateral cerebral hemisphere. Previous research suggests a lateralization of cognitive functions in the cerebellum that mirrors the cerebral cortex, with attention/visuospatial functions represented in the left cerebellar hemisphere, and language functions in the right cerebellar hemisphere. Although there is good evidence supporting the role of the right cerebellum with language functions, the evidence supporting the notion that attention and visuospatial functions are left lateralized is less clear. Given that spatial neglect is one of the most common disorders arising from right cortical damage, we reasoned that damage to the left cerebellum would result in increased spatial neglect-like symptoms, without necessarily leading to an official diagnosis of spatial neglect. To examine this disconnection hypothesis, we analyzed neglect screening data (line bisection, cancellation, figure copying) from 20 patients with isolated unilateral cerebellar stroke. Results indicated that left cerebellar patients (n=9) missed significantly more targets on the left side of cancellation tasks compared to a normative sample. No significant effects were observed for right cerebellar patients (n=11). A lesion overlap analysis indicated that Crus II (78% overlap), and lobules VII and IX (66% overlap) were the regions most commonly damaged in left cerebellar patients. Our results are consistent with the notion that the left cerebellum may be important for attention and visuospatial functions. Given the poor prognosis typically associated with neglect, we suggest that screening for neglect symptoms, and visuospatial deficits more generally, may be important for tailoring rehabilitative efforts to help maximize recovery in cerebellar patients.
Keywords: cerebellum; attention; visuospatial; spatial neglect; CCAS; cerebellar cognitive affective syndrome; fronto-parietal attention network; lateralization of function